PROPER—PRehabilitatiOn Plus Enhanced Recovery after surgery versus enhanced recovery after surgery in gynecologic oncology: a randomized clinical trial. Issue 2 (8th November 2021) - Lopes, Andre; Yamada, Alayne Magalhães Trindade Domingues; Cardenas, Thais de Campos; Carvalho, Jaqueline Nunes de; Oliveira, Emília de Azevedo; Silva, Marina Elisa Ribeiro da; Andrade, Juliana Fenerich Mauri; de Souza Neto, Eduardo; Barros, Lilian Arruda do Rêgo; Costa, Ronaldo Lúcio Rangel
Abstract : Background: Prehabilitation is a process that occurs before surgery and aims to improve patient functional capacity and enhance surgical recovery. This process includes medical, nutritional, physical, and psychological interventions that may reduce the duration of hospital stay and provide postoperative physical benefits. Primary Objective: To evaluate the impact of a prehabilitation program on postoperative recovery time for patients who will undergo gynecological surgery following the Enhanced Recovery After Surgery (ERAS) guidelines. Study Hypothesis: A multidisciplinary, preoperative prehabilitation program for patients who will undergo gynecological surgery leads to a reduction in the length of hospital stay and improves patient functional capacity. Trial Design: Prospective, interventionist, and randomized controlled trial in a 1:1 ratio, open to multidisciplinary team and patients, blinded to surgeons and anesthesiologists. The control group will undergo ERAS standard preoperative care while the intervention group will have ERAS standard preoperative care plus prehabilitation. Major Inclusion Criteria: Patients scheduled to undergo gynecologic surgery performed by laparotomy with a preoperative schedule that allows prehabilitation intervention for 2 to 3 weeks. Primary Endpoint: To compare time between surgery and the day the patient is ready for discharge in patients who underwent the prehabilitation process versus those who did not. Readiness for discharge is defined as the ability to take care of one's-self, to walk alone, and to ingest at least 75% of daily recommended calorie intake. Sample Size: 194 participants Estimated Dates for Completing Accrual and Presenting Results: At present, 30 patients have been recruited. Accrual should be completed by 2023–24. Trial Registration: The study is approved by the IBCC – São Camilo Oncologia ethics committee (reference number 4.256.553) and is registered at clinicaltrials.gov (NCT04596800 ).